Integrating Cultural and Emotional Intelligence to Examine Newcomers’ Performance and Error Reduction: A Moderation–Mediation Analysis - Tesfaye Agafari Bafa; Mingyu Zhang; Chong Chen (Systems)
Built on the Conservation of Resources (COR), Multiple Intelligence (MI), and Social Exchange (SET) theories, this study investigates how cultural intelligence, emotional intelligence, and perceived organizational support influence newcomers’ task performance and error reduction. The research also explores the mediating effects of emotional exhaustion and the moderating effects of cognitive diversity. Data were collected from 476 participants in organizations employing newcomers, using census, stratified, and simple random sampling techniques. Structural Equation Modeling (SEM) was employed to test the research hypotheses. The results reveal that higher levels of cultural and emotional intelligence are negatively associated with emotional exhaustion, while an increase in perceived organizational support reduces emotional exhaustion. Emotional exhaustion was found to be linked to higher error rates and lower task performance. The mediation analyses showed that emotional exhaustion mediated the relationship between cultural intelligence, emotional intelligence, and perceived organizational support and both task performance and error reduction. Furthermore, cognitive diversity moderated the relationships between cultural intelligence and emotional exhaustion, as well as between emotional intelligence and emotional exhaustion. These findings underscore the critical roles of cultural and emotional intelligence, along with organizational support, in mitigating emotional exhaustion, reducing errors, and enhancing task performance, while emphasizing the importance of cognitive diversity in shaping organizational outcomes.